Is Climate-Smart Agriculture effective? A review of selected cases - Dinesh, Dhanush; Frid-Nielsen, Snorre; Norman, James; Mutamba, M; Loboguerrero Rodriguez, Ana María; Campbell, Bruce M. (2015)
Climate-Smart Agriculture (CSA) is an approach to address the interlinked challenges of food security and climate change, and has three objectives: (1) sustainably increasing agricultural productivity, to support equitable increases in farm incomes, food security and development; (2) adapting and building resilience of agricultural and food security systems to climate change at multiple levels; and (3) reducing greenhouse gas emissions from agriculture (including crops, livestock and fisheries). This paper examines 19 CSA case studies, to assess their effectiveness in achieving the stated objectives of CSA, while also assessing other cobenefits, economic costs and benefits, barriers to adoption, success factors, and gender and social inclusion issues. The analysis concludes that CSA interventions can be highly effective, achieving the three CSA objectives, while also generating additional benefits in a costeffective and inclusive manner. However, this depends on context specific project design and implementation, for which institutional capacity is key. The paper also identifies serious gaps in data availability and comparability, which restricts further analysis.